Transforming researchers into writers through a series of semi-structured writing retreats: a mixed methods study - James Bonnamy; Lyndal Bugeja; Julia Morphet; Philip L. Russo; Gabrielle Brand (BMC, 2024)
Abstract Aim To evaluate the experience and effectiveness of six semi-structured writing retreats on research publication quantity and quality for nursing and midwifery academics and research students. Background Research publications are necessary to develop a track record to gain competitive funding and for promotion. Publications also improve the standing of universities because their performance is measured in-part by research outputs. However, there are challenges to writing for publication, especially for new nursing and midwifery academics and research students. Therefore, four of the authors initiated semi-structured writing retreats to support nursing and midwifery academics and research students to overcome these challenges. Methods A mixed methods exploratory sequential design consisting of two distinct phases and data collection methods. In phase one, an online evaluation was administered to collect participant experiences which were then analysed using content analysis. In phase two, data about the quantity and quality of publications arising from each retreat was collected, and descriptive statistics performed. Results A total of 70 participants responded to the online evaluation. Qualitative analysis of their responses demonstrated that the writing retreats were highly valued as they offered a collaborative environment with dedicated time to focus on writing for publication. Quantitative analysis identified 81 publications were planned over the six writing retreats. Of these, 60 have been published, 5 are under review, 5 have not yet been submitted, and 11 were abandoned. Conclusions Findings demonstrated that our six semi-structured writing retreats enabled and developed nursing and midwifery academics and research students writing for publication. Semi-structured writing retreats are a research investment that enabled preparation of high-quality publications by offering protected time to write, expert peer review and collaboration and networking opportunities.